Gendered Process of Women (dis)empowerment in the Community Forestry in Nepal - Baral, Srijana; Tiwari, Sarada; Shrestha, Krishna K (Journal of Forest and Livelihood, 2024)
Women and forest relationships are largely studied in community forestry in Nepal. However, there is a paucity of studies on women's empowerment level in the changed forest management regimes and progressive policies. The study intends to qualitatively analyse women's empowerment using a Women's Empowerment in Agriculture Index (WEAI) tool after modifying it to fit the forestry context i.e. Women's Empowerment in Forestry Index (WEFI) framework. The empowerment parameters, i.e., agency, resources, income, leadership, and time, are used for forest data analysis. The data on the WEFI parameters were collected through semistructured interviews with 45 women representing general members of user groups, executive members of user groups, districts federation and networks of Sindhupalchok and Kavrepalanchok and policy makers as well as ten focus group discussions and observation of key activities during EnLiFT project implementation. The findings reveal that male dominance is high in the access to resources and control over the community forestry decisions. The persistent structural and institutional barriers hinder women's empowerment in community forestry. Unclear policies and ambiguities demotivate women and lower their confidence in engaging themselves in the timber value chain. Moreover, these women have low awareness of their roles and most of them are pseudo-members. Incompatible timings and locations, the technical jargon used in forestry, and having to work with men under societal constructs are hindrances to women's meaningful and worthy participation in community forestry. Despite several positive policy, discriminations, women's access to and control over the economic benefits remains a challenge in community forestry. Hence, institutional innovations for women-friendly community forestry are pertinent to set a conducive pathway for women empowerment.